2019
DOI: 10.1093/jas/skz182
|View full text |Cite
|
Sign up to set email alerts
|

The piglet mycobiome during the weaning transition: a pilot study1

Abstract: The importance of the microbiota in the gastrointestinal tract of animals is recognized as a critical player in host health. Recently, the significance of the mycobiome has been recognized, but culture-independent studies are limited, especially in swine. Weaning is a time of stress, dietary changes, and a predisposition to infections, making it a time point of interest to industry. In this pilot study, we sought to assess and characterize the mycobiome in the feces of swine from birth through the critical wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
55
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 52 publications
8
55
1
Order By: Relevance
“…Results of the current study also revealed a unique fungal composition in the hindgut of piglets. Consistent with previous studies in pigs (Hu et al, 2016;Summers et al, 2019), Ascomycota and Basidiomycota were identified as the two most predominant fungal phyla in the hindgut of piglets, and the two phyla accounted for more than 75% of all fungal populations. As reported in human and mice (Li et al, 2018), Mucoromycota was found as the third abundant fungal phylum in the hindgut of the piglets, suggesting a homogeneous fungal taxonomic composition at phylum level in the gut of pigs, mice and human.…”
Section: F I G U R Esupporting
confidence: 90%
See 3 more Smart Citations
“…Results of the current study also revealed a unique fungal composition in the hindgut of piglets. Consistent with previous studies in pigs (Hu et al, 2016;Summers et al, 2019), Ascomycota and Basidiomycota were identified as the two most predominant fungal phyla in the hindgut of piglets, and the two phyla accounted for more than 75% of all fungal populations. As reported in human and mice (Li et al, 2018), Mucoromycota was found as the third abundant fungal phylum in the hindgut of the piglets, suggesting a homogeneous fungal taxonomic composition at phylum level in the gut of pigs, mice and human.…”
Section: F I G U R Esupporting
confidence: 90%
“…Furthermore, our results showed that genus Kazachstania (Kazachstania slooffiae) belonging to the phylum Ascomycota was the most common fungal genus in the colon, but not in the caecum, of the piglets. Kazachstania has been shown to be a feature of the gut mycobiota in pigs and considered as a natural inhabitant in the gut of pigs (Summers et al, 2019;Urubschurov, Janczyk, Souffrant, Freyer, & Zeyner, 2011 the results of the current study, we still cannot explain whether fungi from the environment could truly colonized in the GI tract of the piglets or were just excreted as transients. Besides, it still remains unknown that whether those dominant fungal species observed in the hindgut of the piglets play a beneficial role to the host and how they interact with the host still remains unknown.…”
Section: F I G U R Ementioning
confidence: 56%
See 2 more Smart Citations
“…Although several studies have explored the fungal communities in human and mice intestines (Suhr and Hallen-Adams, 2015;Li et al, 2017), studies on the composition and diversity of fungi in the intestines of pigs are still very rare. According to the limited results of deep sequencing, Ascomycota and Basidiomycota have been identified as the two most predominant fungal phyla in the faeces of piglets (Hu et al, 2016;Summers et al, 2019), which is consistent with previous findings in the gut of humans and mice. However, Kazachstania slooffae might be the dominant fungal species in weaning piglets (Summers et al, 2019), while its relative abundance showed extremely low or undetectable in the gut of human and mice (Suhr and Hallen-Adams, 2015;Li et al, 2017).…”
Section: Introductionsupporting
confidence: 90%